Effects Of Sodium Dodecyl Sulfate Treated Halloysite Nanotube On The Properties Of Poly(Lactic Acid) Nanocomposites Film - Chiew, Kuan Zheng (Universiti Sains Malaysia, 2017)
Sodium dodecyl sulfate (SDS; loading from 0.6 g to 4.8 g) was used to treat the halloysite nanotube (HNT) in order to increase the compatibility between poly(lactic acid) (PLA) and HNT. From the Fourier Transform Infrared Spectroscopy (FTIR) analysis on the SDS treated HNT, it was found the Si-O Index increased up to 1.8 g SDS and then decreased beyond this loading. This marked the optimum loading of SDS and it gave the HNT to SDS ratio of 1 to 0.36. The PLA/HNT nanocomposite film (thickness in the range of 0.13 mm to 0.15 mm) was prepared using the internal mixer followed by compression molding. The UV blocking ability of the PLA/HNT nanocomposite film was determined using UV-Vis Spectrophotometer. The UV blocking ability of PLA/HNT nanocomposite film increased as the increasing loading of HNT (from 1 wt% to 8 wt%). The PLA/SDS treated HNT-3% nanocomposite film showed higher UV blocking ability than PLA/HNT-3%, with acceptable transparency. The crystallization behaviour of PLA/HNT nanocomposites was studied by using Differential Scanning Calorimeter (DSC). The PLA/SDS treated HNT-3% nanocomposite exhibited a higher degree of crystallinity (XC) than the PLA/HNT-3%. Besides that, the effect of cooling rate (5, 10, 20 and 30°C/min) on the crystallization behaviour of PLA/SDS treated HNT-3% was studied. It was found that the slow cooling rate (i.e., 5oC/min) further increased the XC of the PLA/SDS treated HNT-3% nanocomposite.